Realization of the phenomenon of a dual career in the conditions of integration of sports, educational and scientific activities in universities of physical culture orientation - Petrov, S. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the conditions for the effective implementation of a dual career for student-athletes in the course of integrating sports training into the activities of universities of physical education.